2004
DOI: 10.1002/biof.5520200204
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell factor and H2O2 induce GLUT1 translocation in M07e cells

Abstract: This work aims to elucidate the mechanisms involved in the early activation of glucose transport in hematopoietic M07e cells by stem cell factor (SCF) and a reactive oxygen species (ROS) as H2O2. SCF and H2O2 increase Vmax for glucose transport; this enhancement is due to a higher content in GLUT1 in plasma membranes, possibly through a translocation from intracellular stores. Inhibitors of tyrosine kinases or phospholipase C (PLC) remove glucose transport enhancement and prevent translocation. The inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Figure 2 shows that both the inhibitors diminish the phosphorylation increase induced by SCF and hydrogen peroxide. These results suggest that the activation of the SCF receptor, c-kit, is crucial for the signal pathways elicited by both stimuli and explain the ability of H 2 O 2 to mimic the action of SCF on glucose transport, previously reported (7,21). Cells were incubated in PBS at 37°C in the absence or presence of 5 µM ebselen or 1 µM radical probe [bis(1-hydroxy-2,2,6,6-tetramethyl-4-piperidinyl)decandioate] for 10 min and then treated with SCF (5 ng/ml) for an additional 10 min.…”
Section: Scf and H 2 O 2 Affect Glucose-transport Regulation Through mentioning
confidence: 72%
See 2 more Smart Citations
“…Figure 2 shows that both the inhibitors diminish the phosphorylation increase induced by SCF and hydrogen peroxide. These results suggest that the activation of the SCF receptor, c-kit, is crucial for the signal pathways elicited by both stimuli and explain the ability of H 2 O 2 to mimic the action of SCF on glucose transport, previously reported (7,21). Cells were incubated in PBS at 37°C in the absence or presence of 5 µM ebselen or 1 µM radical probe [bis(1-hydroxy-2,2,6,6-tetramethyl-4-piperidinyl)decandioate] for 10 min and then treated with SCF (5 ng/ml) for an additional 10 min.…”
Section: Scf and H 2 O 2 Affect Glucose-transport Regulation Through mentioning
confidence: 72%
“…1). We previously observed that SCF and H 2 O 2 share the capability to promote Glut1 translocation to the cell membrane (21). We show that both SCF and H 2 O 2 lead to a c-kit-dependent increase in tyrosine phosphorylation and glucose transport.…”
Section: Signal Transduction and Gluti Regulation 275mentioning
confidence: 80%
See 1 more Smart Citation
“…11,[20][21][22][23] These studies have implicated ROS as second messengers involved in mediating signaling from growth factors, such as granulocyte macrophage-colony stimulation factor (GM-CSF) and TPO. 11,20 With the use of a variety of oxidase inhibitors, these studies suggest that Nox's may be the source of ROS in these cell lineages.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that NAD(P)H oxidasederived ROS are required for proliferation of acute leukemia cells, including self-producing VEGF cells (22,28,(33)(34)(35)(36)(37)(38)(39). However, significant work remains to be performed to define the role of each Nox isoform and its regulatory subunits, and to identify molecular targets of oxidase-derived ROS involved in proliferation/viability of leukemic cells.…”
Section: Discussionmentioning
confidence: 99%